A Study on Awareness of AI-Driven Attacks and Dark Web-Generated Threats - Rajapaksha, Sammani (My University, 2024)
A Study on Awareness of AI-Driven Attacks and Dark Web-Generated Threats is a master´s research conducted to study the awareness of employees and students of AI-generated attacks and dark web originated threats. The study aims to discover novel AI-based attacks and dark web-generated threats, study the current level of awareness of the target group, the rationale behind the discovered level of understanding and finally suggest awareness-enhancing methods tailored for individuals. One of the primary purposes of the research is to reduce the gap in cyber security awareness research areas focusing on AI and the dark web. This thesis adheres to empirical research consisting of a literature review, survey and interview to collect data. A hundred participants had completed the survey, and the interviews were conducted from a sub-sample of twelve participants out of that hundred. It was evident that most participants did not have adequate awareness about AI-based attacks or dark web-generated threats. However, compared to each other, the participants had more awareness of dark web threats than novel AI attacks. The participants also explained the reasons behind their positive or negative awareness levels, which are due to social, educational, and personal differences. Suggestions for various awareness-enhancing methods are discussed and proposed using collected data. In conclusion, as evident from the analysis and discussion, the overall awareness of these dangers is not up to a standard. More actions should be taken to develop the awareness of individuals regardless of their study or work fields.
Keywords: Cyber security, Human-computer interaction (HCI), Artificial intelligence, Dark Web, Awareness, Machine Learning, Attacks, Threats, Technology, Students, Employees, Cyber Crime, Privacy, Digital Space